2015
DOI: 10.1002/adhm.201400773
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering: Recent Advances and Perspectives from Gene Regulation/Therapy

Abstract: Diseases in articular cartilages affect millions of people. Despite the relatively simple biochemical and cellular composition of articular cartilages, the self-repair ability of cartilage is limited. Successful cartilage tissue engineering requires intricately coordinated interactions between matrerials, cells, biological factors, and phycial/mechanical factors, and still faces a multitude of challenges. This article presents an overview of the cartilage biology, current treatments, recent advances in the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 320 publications
(405 reference statements)
0
22
0
Order By: Relevance
“…Many biomaterials have been developed that allow for live cell incorporation, but none adequately fulfill all the requirements of an ideal scaffold. 1517 Recently, we reported the use of a water soluble methacrylated polyethyleneglycol-poly-D,L-lactide (mPDLLA-PEG) biodegradable polymer for live cell scaffold fabrication that possessed high mechanical strength (~780 kPa). 18 While this scaffold possessed physiologically relevant mechanical strength on fabrication, we found that after 4 weeks the strength of the cell-seeded scaffold had degraded drastically (~240 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…Many biomaterials have been developed that allow for live cell incorporation, but none adequately fulfill all the requirements of an ideal scaffold. 1517 Recently, we reported the use of a water soluble methacrylated polyethyleneglycol-poly-D,L-lactide (mPDLLA-PEG) biodegradable polymer for live cell scaffold fabrication that possessed high mechanical strength (~780 kPa). 18 While this scaffold possessed physiologically relevant mechanical strength on fabrication, we found that after 4 weeks the strength of the cell-seeded scaffold had degraded drastically (~240 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, significant research activities are directed at treating, augmenting, or repairing degraded cartilage 1923 including, for example, polymer scaffolds for filling tissue defects, 2428 lubricants for improving tribological properties, 29, 30 stimulating growth factors for promoting healing, 31 cell transplantation, 32, 33 and gene therapy for restoring biological activity. 34 An early hallmark of OA is the loss of GAGs with a resultant decrease in the dynamic and equilibrium compressive moduli of the cartilage by allowing increased rate of water exudation and decreased quantity of GAG-bound water, respectively. Furthermore, the hydraulic permeability of cartilage is increased, causing IFLS to decrease at a faster rate upon loading, exacerbating cartilage degeneration by increasing the occurrence of solid-solid contact-derived friction.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with recombinant protein therapy, where factors have short half-lives, gene-based treatments potentially allow for a site-specific action, in a more physiologic manner and with long-term effects [8]. The concept of using gene therapy for cartilage repair originated from the idea that the expression of specific genes into the injury site could increase the regeneration process [9]. Recently, significant advances have been made in the basic science of gene transfer for articular cartilage, with both in vivo (directly delivered to a joint) and ex vivo (retrieved and explanted cells genetically modified in vitro and re-implanted into the joint with or without the use of a scaffold) procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant advances have been made in the basic science of gene transfer for articular cartilage, with both in vivo (directly delivered to a joint) and ex vivo (retrieved and explanted cells genetically modified in vitro and re-implanted into the joint with or without the use of a scaffold) procedures. In vitro cartilage regeneration is effectively promoted by delivering genes that increase cartilage differentiation, as well as by down regulating some negative factors [9].…”
Section: Introductionmentioning
confidence: 99%